Penyebab Kontestasi Negatif Dalam Beragama Di Negara Berbhineka Pada Era Digital - Oka Widana, Anak Agung Gde (Jayapangus Press, 2024)
This research fundamentally aims to build a spirit of optimism and straighten the perspective of religious believers regarding their existence as religious people in a pluralistic country. The three issues that are the focus of attention in this research are related to the causes, consequences and also solutions in overcoming the phenomenon of negative contestation in religion in the digital era in a pluralistic country. As a qualitative research, the data obtained is collected by relying on library techniques and also document recording, where the analysis knife used to dissect the data that has been collected is done through qualitative descriptive techniques. The results of the analysis show that the phenomenon of negative contestation in religion is actually caused by the extreme point of view of the people, egocentric personalities, technological developments, religious populism, excessive freedom of social media, the Three Education Centers (family, school and society) lack of synergy, and national disintegration. This has resulted in the emergence of intolerance, religious arrogance, reduced religious empathy, and disturbed people's mental health. However, this can be overcome through religious moderation, cultivating tolerance intensively, maximizing the collaboration of the Three Centers of Education, refraining from negative debates, improving the quality of religious instructors, tightening supervision of social media, broadening horizons, improving the moral quality of the people, and obeying the rule of law.